Health-related quality of life profiles, trajectories, persistent symptoms and pulmonary function one year after ICU discharge in invasively ventilated COVID-19 patients, a prospective follow-up study. (November 2021) - Gamberini, Lorenzo; Mazzoli, Carlo Alberto; Prediletto, Irene; Sintonen, Harri; Scaramuzzo, Gaetano; Allegri, Davide; Colombo, Davide; Tonetti, Tommaso; Zani, Gianluca; Capozzi, Chiara; Dalpiaz, Giorgia; Agnoletti, Vanni; et al.
Abstract: Background: Health-related quality of life (HRQoL) impairment is often reported among COVID-19 ICU survivors, and little is known about their long-term outcomes. We evaluated the HRQoL trajectories between 3 months and 1 year after ICU discharge, the factors influencing these trajectories and the presence of clusters of HRQoL profiles in a population of COVID-19 patients who underwent invasive mechanical ventilation (IMV). Moreover, pathophysiological correlations of residual dyspnea were tested. Methods: We followed up 178 survivors from 16 Italian ICUs up to one year after ICU discharge. HRQoL was investigated through the 15D instrument. Available pulmonary function tests (PFTs) and chest CT scans at 1 year were also collected. A linear mixed-effects model was adopted to identify factors associated with different HRQoL trajectories and a two-step cluster analysis was performed to identify HRQoL clusters. Results: We found that HRQoL increased during the study period, especially for the significant increase of the physical dimensions, while the mental dimensions and dyspnea remained substantially unchanged. Four main 15D profiles were identified: full recovery (47.2%), bad recovery (5.1%) and two partial recovery clusters with mostly physical (9.6%) or mental (38.2%) dimensions affected. Gender, duration of IMV and number of comorbidities significantly influenced HRQoL trajectories. Persistent dyspnea was reported in 58.4% of patients, and weakly, but significantly, correlated with both DLCO and length of IMV. Conclusions: HRQoL impairment is frequent 1 year after ICU discharge, and the lowest recovery is found in the mental dimensions. Persistent dyspnea is often reported and weakly correlated with PFTs alterations. Trial registration: NCT04411459. Highlights: Little is know about HRQoL long term evolution in COVID-19. In COVID-19 patients requiring ICU, HRQoL is impaired 1 year after acute phase. The lowest recovery 1 year after COVID-19 emerged in mental dimensions. Persistent dyspnea is reported in more 50% of patients 1 year after COVID-19. Impairment in pulmonary function weakly explains the entity of dyspnea complained.